DEFINE EXTRACTION METHOD TO OBTAIN POSSIBLE HIGHEST CONTENT OF YIELD RECOVERY OF THE RICE VOLATILE COMPOUNDS - Zahara Mardiah; Bram Kusbiantoro; Riane Rizky (Widyariset, 2012)
2-Acetyl-1-pyrroline (2-AP) is the most important compound in aromatic rice that correlated with the quality of the aroma, therefore, determination of 2-AP concentration become very important. This research aims to find the extraction method to obtain the highest yield recovery of 2-AP. The materials used were H51 and Segara Anak to treatments test, and Pandan wangi, Sariwangi, Sintanur, and Gilirang for comparison the methods. Analysis using SPME method with three types of sample treatment, i.e. 80 mesh flour, 45 mesh flour, and cooked rice. While the analysis using Likens Nickerson with a different anti-foaming agent (MgSO4 and silicon) and a different ratio of rice and water (1:2 and 1:3). Extract samples were analyzed using Gas Chromatography Mass spectrometry (GCMS). The best results of any treatment will be used in a comparison test between the two extraction methods. The sample type of 45 mesh powder on SPME method (SPME-opt) and silicon as an anti foaming agent as well as rice and water ratio 1:3 on the Likens Nickerson method (Likens Nickerson-opt) is the best treatment in determining the yield recovery of 2 - AP. Comparison test indicated that SPME-opt is better than Likens Nickerson-opt in obtain the yield recovery of 2-AP.